PERANCANGAN SISTEM INFORMASI SURAT KETERANGAN KEMATIAN BERBASIS WEB DI RSU NURHAYATI GARUT - Putri Aulia Alandra Zen (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The development of technology influences a system that is manual to become a computerized-based system, especially in medical records that provide opportunities for high-quality health services andefficiencyn. The information system for medical records of death certificates in the wards of the Inpatient Unit and the Emergency Installation unit (IGD) at Hospital Nurhayati Garut is still carried out manually so that there is less accuracy in the process of recording data, managing data, recapitulation of deaths, and reporting patient death data. Death certificates have been regulated by the Ministry of Health in terms of formats and procedures for spending, but in its implementation there are still many hospitals that do not comply with these regulations. The purpose of this study is to simplify the process of making a death certificate for use by the families left behind as well as for the benefit of epidemiological data. This method of designing a death information system uses the Extreme Programming method which is the stages of planning, design, coding, testing. The result of the study is a web-based Information System with the programming language used, namely PHP, the web server source uses XAMPP (Apache and MySQL), the database used is MySQL and the text editor used sublime Text 3 and the Bootsrap framework in managing patient death information data accurately so as to produce quality letters and death data reports.